Ag‐induced Phase Transition of Bi2O3 Nanofibers for Enhanced Energy Conversion Efficiency towards Formate in CO2 Electroreduction. Issue 2 (2nd January 2023) - Wang, Xin; He, Wenhui; Shi, Jialin; Junqueira, João R. C.; Zhang, Jian; Dieckhöfer, Stefan; Seisel, Sabine; Das, Debanjan; Schuhmann, Wolfgang
Abstract: Bi‐based electrocatalysts have been widely investigated in the CO2 reduction reaction (CO2 RR) for the formation of formate. However, it remains a challenge to achieve high Faradaic efficiency (FE) and industrial current densities at low overpotentials for obtaining both high formate productivity and energy efficiency (EE). Herein, we report an Ag−Bi2 O3 hybrid nanofiber (Ag−Bi2 O3 ) for highly efficient electrochemical reduction of CO2 to formate. Ag−Bi2 O3 exhibits a formate FE of >90% for current densities from −10 to −250 mA ⋅ cm −2 and attains a yield rate of 11.7 mmol ⋅ s −1  ⋅ m −2 at −250 mA ⋅ cm −2 . Moreover, Ag−Bi2 O3 increased the EE (52.7%) by nearly 10% compared to a Bi2 O3 only counterpart. Structural characterization and in‐situ Raman results suggest that the presence of Ag induced the conversion of Bi2 O3 from a monoclinic phase (α‐Bi2 O3 ) to a metastable tetragonal phase (β‐Bi2 O3 ) and accelerated the formation of active metallic Bi at low overpotentials (at > −0.3 V), which together contributes to the highly efficient formate formation. Abstract : A novel Ag−Bi2 O3 electrocatalyst for the CO2 reduction reaction was synthesized by electrospinning. Employed in a gas‐diffusion electrode, it shows high Faradaic efficiency for formate production at high current densities with low overpotentials, high formate formation rate, and high energy conversion efficiency. Structural characterizations and in‐situ Raman indicate that phase change from monoclinic α‐Bi2 O3 to metastable tetragonal β‐Bi2 O3 accelerated the formation of formate.